What is the Value of Luxury? A Cross-Cultural Consumer Perspective - Hennigs, Nadine; Wiedmann, Klaus-Peter; Klarmann, Christiane; Strehlau, Suzane; Godey, Bruno; Pederzoli, Daniele; Neulinger, Agnes; Dave, Kartik; Aiello, Gaetano; Donvito, Raffaele; Taro, Koyama; Táborecká-Petrovičová, Janka; et al. (Psychology & marketing, 2012)
ABSTRACT International luxury businesses are challenged by the identification and satisfaction of the common needs and desires of global market segments. Although luxury goods have become available to a wider range of consumers, the traditional conspicuous consumption model has been transformed into a new experiential luxury sensibility that is marked by a change in the way that consumers define luxury. Based on an empirical study in collaboration with American, European, and Asian researchers, the results provide evidence that consumers in various parts of the world purchase or wish to purchase luxury products for varied reasons but that such consumers generally possess similar values. Regardless of their countries of origin, the basic motivational drivers of luxury consumers are similar among the financial, functional, personal, and social dimensions of luxury value perceptions, although the relative importance of these dimensions varies.